The Missing Middle? General and Special Educators’ Views of Effective Mathematics Instruction - Julie Cohen; Nathan Jones; Lynsey Gibbons (AERA Open)
General educators rarely receive adequate training for supporting students with disabilities (SWDs). We suggest a key contributing factor is the longstanding gap between special and general education researchers, which is especially pronounced in mathematics. Researchers from these fields work in isolation from one another, the result of what sociologists term “epistemic bunkers.” These cross-field divisions have pragmatic consequences. Well-established teaching strategies known to support SWDs are untouched in general teacher education. At the same time, prospective special educators lack exposure to many key instructional principles from mathematics education. In this interview study, 22 general and special education researchers describe their goals for mathematics education. Our data suggest considerable within-group heterogeneity, but also clear within-group themes and between-group distinctions. There were numerous points of intersection between special and general educators’ perspectives on mathematics teaching and learning, providing clear opportunities for bridge building. We conclude with implications for research and practice.